International Law Enforcement Cooperation against Money Laundering - Steblianko, Alina V.; Chernadchuk, Tamara O.; Kravchenko, Ivan O.; Andriichenko, Nadiia S.; Rudanetska, Oksana S. (Cuestiones Políticas, 2020)
The purpose of the article is to focus on the need to strengthen the interaction of the law enforcement agencies of various states, highlighting the role of financial institutions in this process, to find optimal ways to improve international cooperation. The study is based on the methods of systemic and critical analysis, as well as a formal logical method. The article confirms that the need to strengthen international cooperation is explained by the existence of certain factors that determine the possibility of money laundering. It has been established that without adequate cooperation between law enforcement agencies and financial institutions at the national level, it is quite difficult to detect crime and prevent money laundering at the initial stage. As a conclusion of the investigation, it is proposed to develop a methodology for the interaction of the law enforcement agencies of several states to counteract money laundering. The results obtained can also become the basis for developing legislative proposals to improve international cooperation in law enforcement and, at the same time, they can be used to increase the efficiency of their anti-money laundering activities.